Akuntabilitas Pelayanan Penerimaan dan Verifikasi Laporan On The Spot (PVL OTS) Dalam Pencegahan Maladministrasi Penyelenggara Pelayanan Publik Oleh Ombudsman Republik Indonesia Perwakilan Provinsi Bali - Pande Kadek Kusumadewi; I Dewa Ayu Putri Wirantari; Putu Anik Prabawati (CV. Lenggogeni Data Publishing, 2024)
The reception of public complaints by the Ombudsman of the Republic of Indonesia must of course be accountable for the preparation, implementation and evaluation of the implementation of on the spot report reception and verification services (PVL OTS). The aim of this research is to analyze and describe the theory of accountability in the On The Spot Report Reception and Verification (PVL OTS) service in preventing maladministration by public service providers by the Ombudsman of the Republic of Indonesia representing Bali Province. This research uses a descriptive qualitative type. The results of this research show that the service for receiving and verifying reports on the spot (PVL OTS) has been running quite well in terms of the five indicators of accountability dimensions. However, there are still several obstacles in implementing reception services, such as the lack of public knowledge regarding the implementation of PVL OTS, the lack of Human Resources, the lack of PVL OTS facilities, and the lack of time for implementing PVL OTS. The recommendations that can be given are to increase socialization to people who have minimal internet access, make legal regulations regarding the number of human resources (HR) in each assistantship based on the weight of each assistantship's tasks, make a community satisfaction survey regarding the implementation of PVL OTS, and for agencies. Public services that are used as venues for implementing PVL OTS should have a high level of commitment to help make the program a success. Abstrak Penerimaan pengaduang masyarakat oleh Ombudsman Republik Indonesia tentunya harus dapat dipertanggungjawabkan baik dari penyusunan, pelaksanaan dan juga evaluasi dari pelaksanaan pelayanan penerimaan dan verifikasi laporan on the spot (PVL OTS). Tujuan dari penelitian ini yaitu menganalisis serta mendeskripsikan teori akuntabilitas pada pelayanan Penerimaan dan Verifikasi Laporan On The Spot (PVL OTS) Dalam Pencegahan Maladministrasi Penyelenggara Pelayanan Publik oleh Ombudsman Republik Indonesia Perwakilan Provinsi Bali. Penelitian ini menggunajan jenis kualitatif deskriptif. Hasil dari penelitian ini menunjukan bahwa pelayanan penerimaan dan verifikasi laporan on the spot (PVL OTS) sudah berjalan cukup baik dari lima indikator dimensi akuntabilitas. Namun masih terdapat beberapa kendala dalam pelaksanaan pelayanan penerimaan seperti minimnya pengetahuan masyarakat terkait pelaksanaan PVL OTS, minimnya Sumber Daya Manusia, minimnya fasilitas PVL OTS, dan kurangnya waktu pelaksanaan PVL OTS. Adapun rekomendasi yang dapat diberikan yaitu lebih meningkatkan sosialisasi ke masyarakat yang minim mengakses internet, membuat aturan hukum mengenai jumlah sumber daya manusia (SDM) di setiap keasistenan berdasarkan bobot tugas masing-masing keasistenan, membuat survei kepuasan masyarakat terkait pelaksanaan PVL OTS, dan untuk instansi pelayanan publik yang dijadikan tempat pelaksanaan PVL OTS hendaknya memunyai komitmen yang tinggi untuk membantu menyukseskan program tersebut. Kata Kunci: Akuntabilitas, pelayanan publik, Ombudsman Republik Indonesia